Unidirectional alteration of methylation and hydroxymethylation at the promoters and differential gene expression in oral squamous cell carcinoma - Zhao, Weizhi; Zhu, Lin; Gong, Qian; Ma, Suzhen; Xiong, Haofeng; Su, Tong; Wan, Zhengqing; Wang, Danling (Frontiers in Genetics, 2023)
Background: Oral squamous cell carcinoma (OSCC) is one of the most common types of cancer worldwide. Although overall losses of 5 methylcytosine (5mC) and 5 hydroxymethylcytosine (5hmC) have been previously observed, a genome wide, single base resolution, and simultaneous mapping of 5mC and 5hmC in OSCC is still unaccomplished. Similarly, the mechanism of how 5mC and 5hmC collectively lead to abnormal gene expression in OSCC is largely unexplored. Using parallel whole genome bisulfite sequencing (WGBS) and whole genome oxidative bisulfite sequencing (oxWGBS), we characterized 5mC and 5hmC profiles at single nucleotide resolution in paired primary OSCC samples and their normal adjacent tissues (NATs). We also analyzed the effect of 5mC and 5hmC modifications on differential gene expression in OSCC using multi omics analysis. Results: An overall reduction of both 5mC and 5hmC in various genomic regions have been observed in OSCC samples. At promoter regions, a total of 6,921 differentially methylated regions and 1,024 differentially hydroxymethylated regions were identified in OSCC. Interestingly, compared to bidirectional modification with 5mC and 5hmC, unidirectional modification with 5mC and 5hmC at the promoters is associated with bigger change in the gene expression. Additionally, genes bearing unidirectional modification with 5mC and 5hmC at the promoters are enriched in signaling pathways like cell proliferation, cell differentiation, and receptor tyrosine kinase pathway that are essential for the tumorigenesis. Finally, the grouped expression signature of top 20 genes bearing promoter unidirectional modification with 5mC and 5hmC tends to correlate with the clinical outcome of certain subtypes of head and neck squamous cell carcinoma. Conclusions: Using parallel WGBS and oxWGBS analyses, we observed an overall reduction of 5mC and 5hmC modifications at various genomic regions in OSCC. Unidirectional modification with 5mC and 5hmC at the promoters is associated with enhanced changes in gene expression in OSCC tissues. Furthermore, such differentially expressed genes bearing unidirectional modifications with 5mC and 5hmC at the promoters might have clinical relevance to the outcome of OSCC.